Risk management practice and risk disclosure on financial performance in Islamic and conventional banks in GCC countries - Al Ali, Hussain (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
Risk management is regarded as one of the most interesting and deeply researched areas over the past 15 years in the financial industry. Risk management in the financial sector is crucial as many banks argue that shareholder value is established through superior risk management. The global economic crisis broke out in the United States in 2008 as a result of the bankruptcy of the most well-established and prominent U.S. banks, followed by the bankruptcy of several banks all over the world. The spread of the crisis to almost the whole world has raised many questions about the effectiveness of risk management practice applied by those bankrupt banks. The findings reached by several studies have actually proved the failure of risk management departments to effectively perform their duties. Risk management experts, practitioners, academicians, and others acknowledge that the presence of effective risk management departments is the cornerstone for the management of economic and financial institutions, including banks, while the failure of effective risk management practice may lead to effect negatively on financial performance for institutions, including banks. As the GCC countries is an indispensable part of the world, the researcher embarked on this study with the aim of examining the risk management practice, risk disclosure, and financial performance (ROA and ROE) of both Islamic and conventional banks in the GCC countries. The researcher also investigated the impact of risk management practice and risk disclosure on the banks' financial performance (ROA and ROE). The study selected a sample of 30 out 61 banks from five counties (14 Islamic banks and 16 conventional banks). The present study used a quantitative approach with primary data (questionnaires) and secondary data (the annual reports for 30 banks for the years 2008 to 2013). Data was analysed by using various statistical tests, such as descriptive, T-test, regression, the ANOVA test, and cross-sectional and panel data. The findings of the study indicated that there are statistically no differences in risk management practice and risk disclosure between Islamic and conventional banks. However, there is positively influence of risk management practice on the financial performance of the Islamic banks in the GCC countries. Meanwhile, it was found that risk disclosure has no influence on the both Islamic and conventional banks on financial performance in the GCC countries. Moreover, risk disclosure for Islamic and conventional banks in the GCC countries are almost the same. When statistically comparing between the two types of banks, the mean for risk disclosure for conventional banks is slightly higher than Islamic banks in the GCC countries. This study creates significant contribution from at least three perspectives; contribution to knowledge, contribution to practice and lastly contribution to policies and regulations. In term of knowledge, a few studies– to the best of the researcher's knowledge – were conducted in the GCC countries related only to risk management practice and the study adds interesting insight from the point of view of academics and practitioners. In term of practice, the study provides empirical analysis to practitioners and bank managers on the consequence of driving factors that may assist them extend the performance of the banking system and advance the excellence of services thereby adding value to the banking sector. In term of policies and regulations, Islamic banks need a special regulation to be established, where it regulates and supervises Islamic banks, and is responsible for regulating these banks in terms of Shari'ah compliance principles.